Expanding the clinical spectrum of hereditary fibrosing poikiloderma with tendon contractures, myopathy and pulmonary fibrosis due to FAM111B mutations. Issue 1 (December 2015) - Mercier, Sandra; Küry, Sébastien; Salort-Campana, Emmanuelle; Magot, Armelle; Agbim, Uchenna; Besnard, Thomas; Bodak, Nathalie; Bou-Hanna, Chantal; Bréhéret, Flora; Brunelle, Perrine; Caillon, Florence; Chabrol, Brigitte; et al.
Abstract Background Hereditary Fibrosing Poikiloderma (HFP) with tendon contractures, myopathy and pulmonary fibrosis (POIKTMP [MIM 615704]) is a very recently described entity of syndromic inherited poikiloderma. Previously by using whole exome sequencing in five families, we identified the causative gene, FAM111B (NM_198947.3), the function of which is still unknown. Our objective in this study was to better define the specific features of POIKTMP through a larger series of patients. Methods Clinical and molecular data of two families and eight independent sporadic cases, including six new cases, were collected. Results Key features consist of: (i) early-onset poikiloderma, hypotrichosis and hypohidrosis; (ii) multiple contractures, in particular triceps surae muscle contractures; (iii) diffuse progressive muscular weakness; (iv) pulmonary fibrosis in adulthood and (v) other features including exocrine pancreatic insufficiency, liver impairment and growth retardation. Muscle magnetic resonance imaging was informative and showed muscle atrophy and fatty infiltration. Histological examination of skeletal muscle revealed extensive fibroadipose tissue infiltration. Microscopy of the skin showed a scleroderma-like aspect with fibrosis and alterations of the elastic network.FAM111B gene analysis identified five different missense variants (two recurrent mutations were found respectively in three and four independent families). All the mutations were predicted to localize in the trypsin-like cysteine/serine peptidase domain of the protein. We suggest gain-of-function or dominant-negative mutations resulting in FAM111B enzymatic activity changes. Conclusions HFP with tendon contractures, myopathy and pulmonary fibrosis, is a multisystemic disorder due to autosomal dominantFAM111B mutations. Future functional studies will help in understanding the specific pathological process of this fibrosing disorder.